2009
DOI: 10.1270/jsbbs.59.595
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the genus Hordeum using thioredoxin-like gene sequences

Abstract: Phylogenetic relationships within the genus Hordeum were investigated based on nucleotide sequences of the thioredoxin-like (HTL) gene. We analyzed amplified genomic DNA fragments of the HTL gene from 11 Hordeum species including 16 taxa (25 accessions), which cover mainly diploid accessions together with several tetraploid accessions. Phylogenetic analysis based on the HTL sequences demonstrated a clear divergence of the four basic genomes I (H. vulgare and H. bulbosum), Xa (H. marinum), Xu (H. murinum) and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Particularly DNA sequencing resulted in fast advances in molecular phylogenetics of the genus during the last decade (Komatsuda et al 1999, Nishikawa et al 2002, Petersen and Seberg 2003, Blattner 2004, 2006, Jakob and Blattner 2006, Kakeda et al 2009, Sun et al 2009). …”
Section: Phylogenetic Analyses In Hordeummentioning
confidence: 99%
See 3 more Smart Citations
“…Particularly DNA sequencing resulted in fast advances in molecular phylogenetics of the genus during the last decade (Komatsuda et al 1999, Nishikawa et al 2002, Petersen and Seberg 2003, Blattner 2004, 2006, Jakob and Blattner 2006, Kakeda et al 2009, Sun et al 2009). …”
Section: Phylogenetic Analyses In Hordeummentioning
confidence: 99%
“…Taking into account the importance of barley, surprisingly few phylogenetic studies of Hordeum with a complete or at least representative taxon sample were conducted. Studies with higher species numbers or including at least most diploid species have been published by Jørgensen (1986), Doebley et al (1992), Komatsuda et al (1999), Provan et al (1999), Nishikawa et al (2002), Seberg (2003, 2004), Blattner (2004Blattner ( , 2006, Jakob and Blattner (2006), Kakeda et al (2009), andSun et al (2009). The results were partly contradictory, due to (i) inconsistencies between chloroplast and nuclear phylogenies, (ii) differences in taxon sampling, (iii) incongruence among specific loci, and (iv) different analysis methods.…”
Section: Phylogenetic Analyses In Hordeummentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies showed H. murinum as a closely related species to H. vulgare (e.g., Taketa et al 1999;El-Rabey et al 2002;Blattner 2004Blattner , 2009Kakeda et al 2009). H. murinum possessing a center of diversity in Mediterranean region, is an annual, inbreeding di-, tetra-and hexaploid species occurring with three subspecies: murinum (2n = 4x = 28), glaucum (Steudel) Tzvelev (2n = 2x = 14), and leporinum (Link) Arcangeli (2n = 4x,6x = 28,42).…”
Section: Introductionmentioning
confidence: 99%